HUBUNGAN ANTARA EFEKTIVITAS KOMUNIKASI ANTARPRIBADI FASILITATOR CSR DAN TINGKAT KEPERCAYAAN PENERIMA MANFAAT DENGAN REPUTASI PERUSAHAAN PT. INDONESIA POWER SEMARANG PGU - Siti Ahmaniar Cahya Lestari; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The problem communication such as misunderstanding, there is no feedback, and the ineffectiveness of a message often occurs while the company communicates or interacts with stakeholders, moreover runs the CSR program. The problems of communication above affected one of the CSR goals that cannot achieve in the maximum. It is CSR can improve the living standards of people that are living in the region around the company like happened in the District of North Semarang because it has the highest poverty rate in the Semarang city. Not achieve the CSR objectives will because residents who live around the company have poor judgments against the company and have no trust against the company and so, causes a poor reputation against the company. Moreover, if the company has excessive gas emission and one of them is PT. Indonesia Power Semarang PGU. The research has a purpose determines if there is a relations between the effectiveness of interpersonal communication done by the facilitator of CSR and the level of trust beneficiaries with the reputation company of PT. Indonesia Power Semarang PGU. This research is a quantitative research using the theory of the effectiveness of communication interpersonal and theory of reasoned action (TRA). Sample this research is Group guidance of PT. Indonesia Power Semarang PGU that the Joint Business Group (KUB) Prima Indosutera in the District of North Semarang. Based on the results of the research is, the effectiveness of interpersonal communication and the level of trust beneficiaries have significant relations to the company’s reputation. The things above showed through the significance value of the hypothesis test performed, more effective the communication interpersonal has done so, the company’s reputation is better (positive) that such a hypothesis has a significance value of 0.000 (0,000 s of 0.01).